Clonal Relatedness of Erythromycin-Resistant Streptococcus pyogenes Isolates in Germany - Reinert, Ralf R. (Antimicrob Agents Chemother, 2004)
In a nationwide study in Germany, a total of 381 Streptococcus pyogenes were collected. Erythromycin A-resistant strains were characterized for the underlying resistance genotype, showing 55.6% had the efflux type mef(A), 31.5% had erm(A), and 13.0% had erm(B). A total of 23 different multilocus sequence types were observed.